Mathematics of Program Construction 11th International Conference, MPC 2012, Madrid, Spain, June 25-27, 2012. Proceedings - Gibbons, Jeremy; Nogueira, Pablo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 11th International Conference on Mathematics of Program Construction, MPC 2012, held in Madrid, Spain, in June 2012. The 13 revised full papers presented together with three invited talks were carefully reviewed and selected from 27 submissions. The papers are organized in topical sections on security and information flow, synchronous and real-time systems, algorithms and games, program calculi, tool support, algebras and datatypes, and categorical functional programming.
Keywords: Computer science; Software engineering; Logic design; Computational complexity; Computer Science; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Software Engineering; Discrete Mathematics in Computer Science; Programming Languages, Compilers, Interpreters; Math Applications in Computer Science